The Study of a Contextual Model of People-Centered Inclusive Humanitarian Action: Case Study in Cianjur, West Java and Sigi, Central Sulawesi, Indonesia - Koesuma, Sorja; Pelupessy, Dicky C; Mariany, Aria; Paripurno, Eko Teguh; Silvanto, Tri; Purnama, Anton Roy (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2024)
Indonesia needs progressive changes that are adapted to the global disaster management framework as well as a reflection of humanitarian practices to build humanitarian action that is inclusive, accountable, and people-centered. People-Centered Inclusive Humanitarian Action (PCIHA) aims to establish a disaster management model that is inclusive of persons with disabilities and follows the regional context in Indonesia. The PCIHA implementation model is adopted from the Guidelines on Inclusion of Persons with Disabilities in Humanitarian Action. It has four mandatory components used as principles in its implementation: 1) Performing data aggregation, 2) eliminating inhibiting factors, 3) promoting participation, and 4) empowering persons with disabilities. These four components are one unit that is intertwined and cannot be separated. The model implementation is carried out using a data aggregation approach as the initial entry point for implementing the other three pillars. The results obtained are differences between the data obtained and data from the Village Government. This can affect many things, especially in decision-making related to risk reduction and disaster management policies. The involvement of local organizations of persons with disabilities is needed to realize inclusiveness, which is carried out by understanding how local communities, including persons with disabilities, can be actively involved in humanitarian response when facing disasters.